STUDIES ON FREEZING AND STORAGE OF PSENOPSIS CYANEA - PERIGREEN, P A; JOSEPH, JOSE; GEORGE, CHINNAMMA (Fishery Technology, 2017)
The freezing and storage characteristics of Psenopsis cyanea caught on board FORV Sagar Sampada from a depth of 350 m off Cochin are reported. The fat content of the fish was high (15.58% on the weight of whole fish) and the meat was white in colour. Peroxide value, free fatty acids and thiobarbituric acid values increased during frozen storage and organoleptically the fish was acceptable upto 32 weeks at - 22Â±1Â°C.